FACTORS AFFECTING SELF CARE MANAGEMENTS: COVID-19 BOOSTER VACCINATION PROGRAM IN THE WORKING AREA OF TLOGOSARI KULON PUSKESMAS, SEMARANG - Niken Niken; MA Ermi Tri; Kristiana Kristiana; Apolonia Apolonia; Regina Lany (Sean Institute, 2022)
This study aims to analyze and describeefforts issued by the government in reducing the increase in cases of covid 19 in Indonesia, and many of these have been carried out, one of which is with 5M discipline and continuous vaccination campaigned by the government. The vaccination program itself has been carried out in all cities and villages. Of course, with efforts so that the Covid 19 case can be suppressed. This research is a quantitative analytic study with a cross sectional design and uses chi square statistical tests (bivariate) and logistic regression (multivariate). The population is all residents of RT 05 RW XVI Tlogosari Kulon Semarang. Sampling in this study using total sampling. Research tools and materials used by researchers are screening sheets and questionnaire sheets.